Mathematical analysis of casson fluid flow with energy and mass transfer under the influence of activation energy from a non-coaxially spinning disc - Alqarni, M. M.; Bilal, Muhammad; Allogmany, Reem; Tag-Eldin, Elsayed; Ghoneim, Mohamed E.; Yassen, Mansour F. (Frontiers in Energy Research, 2022)
Casson fluid is the most suitable rheological model for the blood and other non-Newtonian fluid problems. Casson fluid holds yield stress and has great significance in biomechanics and polymer industries. In current analysis, the numerical simulation of non-coaxial rotation of the Casson fluid over circular disc is estimated. The influence of thermal radiation, second order chemical reaction, buoyancy and heat source in rotating frame over a Casson fluid is studied. Time evolution of secondary and primary velocities, solute particles and energy contour are examined. The varying intensity of magnetic flux is applied on the fluid flow. A nonlinear sequence of partial differential equations is used to describe the phenomenon. The modeled equations are reduced to a nondimensional set of ODEs using similarity replacement. The obtained sets of ODEs are further simulated using the parametric continuation method (PCM). The impact of physical constrains on energy, concentration and velocity profiles are presented through figures and tables. It has been noted that the effect of Casson fluid coefficient, Grashof number and magnetic field reduces the fluid primary velocity contour. Furthermore, the mass transfer field lessens with the action of constructive chemical reaction, while augments with the upshot of destructive chemical reaction. The flourishing trend of Schmidt number drops the mass profile, while enhances with the growing values of activation energy and Soret number.